Biblical Theology of Life in the Old Testament - Coetsee, Albert J. (Reformed Theology in Africa Series, 2021)
Life is a primary theme in Scripture, expressed in the rich diversity of the various books, corpora and genres of Scripture. Much has been published on what Scripture teaches about life and death. To date, however, no comprehensive biblical theology in which the concept of life is traced throughout the different books and corpora of the Old and New Testament has been published. It is this lacuna that this book aims to fill, assuming that such an approach can provide a valuable contribution to the theological discourse on life and related concepts. The primary aim of this book is to give an indication of the different nuances of the concept of life in the various books and corpora of the Old and New Testament by providing the reader with a book-by-book overview of the concept of life in Scripture. The secondary aim is to give an indication of the overall use and function of the concept of life in the Old Testament, the New Testament, and Scripture as a whole. The latter is provided by using the findings of the book-by-book overview of the concept of life in Scripture to draw the lines together